The Social Trends of Indonesian Micro, Small and Medium Enterprises (MSME): Public Trust, Halal Fatwas, and Practical Implication - Jadid, Bader Fahad A Bin; Hidayat, M.; Abdillah, Abdillah; Rais, M. Fauzi (Graduate School of Syarif Hidayatullah State Islamic University Jakarta, 2024)
The Indonesian economy is significantly driven by Micro, Small, and Medium Enterprises (MSMEs), which face challenges related to halal certification. The Indonesian Ulema Council (MUI) plays a crucial role in providing halal fatwas through a self-declaration mechanism for MSMEs. This study explores the challenges MSMEs encounter in obtaining halal fatwas and their impact on consumer purchase decisions. From a self-declaration perspective, the MUI validates and issues halal fatwas for MSME products. Although self-declaration aims to ease the certification process, challenges such as high costs and difficulty meeting standards persist. However, the MUI's role in providing credible halal fatwas and maintaining public trust is vital. This research uses a library study method, analyzing data from primary legal materials, relevant literature, survey results, and other information. The findings indicate that self-declared halal fatwas can enhance consumer trust in MSME products, though concerns about the validity of such certifications remain due to the lack of audits and formal fatwa determinations.